2022
DOI: 10.1001/jama.2022.5448
|View full text |Cite
|
Sign up to set email alerts
|

Long-Acting Reversible Contraception With Contraceptive Implants and Intrauterine Devices

Abstract: This JAMA Insights discusses long-acting reversible contraception, including implants and IUDs, and special considerations that clinicians should take into account when approaching contraceptive counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Similarly, more malpositioned IUDs were observed in the early placement group compared with the interval group; the clinical significance of malpositioned IUDs is also unclear, especially in the absence of symptoms. 18 However, an ectopic pregnancy was diagnosed in a participant with a malpositioned hormonal IUD. This study observed higher risk differences for expulsion in the per-protocol analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, more malpositioned IUDs were observed in the early placement group compared with the interval group; the clinical significance of malpositioned IUDs is also unclear, especially in the absence of symptoms. 18 However, an ectopic pregnancy was diagnosed in a participant with a malpositioned hormonal IUD. This study observed higher risk differences for expulsion in the per-protocol analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown whether partially expelled IUDs retain some effectiveness and whether this differs by IUD type (copper vs hormonal); however, an intrauterine pregnancy was diagnosed in a participant with a partially expelled copper IUD. Similarly, more malpositioned IUDs were observed in the early placement group compared with the interval group; the clinical significance of malpositioned IUDs is also unclear, especially in the absence of symptoms . However, an ectopic pregnancy was diagnosed in a participant with a malpositioned hormonal IUD.…”
Section: Discussionmentioning
confidence: 99%
“…In Reply We agree with Drs Gao and Zhang that understanding the effectiveness of IUDs to prevent pregnancy is important to adequately weigh the risks and benefits of early postpartum IUD placement. Although IUDs are well known to be highly effective, our study was not designed to adequately assess the effectiveness of early postpartum IUDs for pregnancy prevention. We did report all pregnancies in the trial; 2 pregnancies occurred during use of an IUD among the 294 participants who received an IUD and completed 6-month follow-up (1 in the early placement group and 1 in the interval placement group).…”
mentioning
confidence: 99%